Fertilizer effect and a model for forecasting yields - Lauri Kettunen; Tuomo Heikkilä; Antti Jaakkola (Agricultural and Food Science, 1981)
A simulation model for forecasting the development of crop yields is built in the article. A parabolic function is applied to represent the fertilizer effect on yields. The biological-technological development is taken into account by including the time factor into the yield function. The parameters of the functions are estimated from the data obtained from field experiments. The economic optimum determines the use of fertilizers which, in turn, is needed to calculate final forecasts of yields for each year. The user of the model may freely select the growth rate of the fertilizer price. The rise in production costs is compensated to the farmers by raising producer prices accordingly.